Wind Energy Development Policy as a Type of Alternative Renewable Energy Sources - ABRAMOVSKIY, Anton L.; SHALIN, Victor V.; SHESTAKOV, Sergey A. (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.v10.5(37).01, 2019)
The relevance of the article is justified by the growing interest in alternative energy sources due to the limited reserves of fossil fuels and environmental pollution. The advantages of wind energy are presented: no need for any fuel, economic benefits, energy independence, and environmental safety. The process of obtaining electricity from the wind is considered. Comparison of wind turbines with battery and wind turbines without battery and comparison of wind turbines and power lines is conducted. Based on the analysis of the calculation results, it was concluded that a wind turbine without a battery is more economical than a wind turbine with a battery. In particular, the prospects for the use of wind power in the Arctic zone and in remote areas of the Russian Federation are considered. It is concluded that for residents of remote areas it is more economically feasible to use wind power plants as compared to traditional types of energy. The legislative and economic barriers to the development of wind energy as a type of non-traditional renewable energy sources are identified, and mechanisms for overcoming them are proposed. The article brings significant contribution in the field of political sociology both in its practical and theoretical aspects, being addressed to the politicians, scientists and management staff involved in this area of knowledge.